Biograf, czyli kto? Spór o Kapuścińskiego non-fiction - Galant, Arleta (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article reconstructs selected problems of critical and publicistic discussion around Artur Domosławski’s book Kapuściński non-fiction concerning the status of the biographical narrative, the role and duties of the biographer and the limits of biographical disclosures. The themes discussed in this sketch made it possible to indicate current issues related to workshop deficiencies and duties of the contemporary biographer, including the exposition of issues related to modernity, subjectivity and ethics of biographical undertakings.